Perceived paternal emotional fertility intention and its correlates in Ethiopia among a cohort of pregnant women: Community based longitudinal survey; A secondary data analysis of the 2019/20 baseline survey - Solomon Abrha Damtew; Mahari Yihdego Gidey; Niguse Tadele Atnafu; Fitsum Tariku Fantaye; Kelemua Mengesha Sene; Bezawork Ayele Kassa; Hailay Gebremichael Gebrekidan; Tariku Tesfaye Bekuma; Seifu Yenneda Berhe; Gelane Duguma Edosa; Temesgen Bati Gelgelu; Wakgari Binu Daga; et al. (PLoS ONE, 2025)
Background Perceived paternal emotional fertility intentions were measured by asking pregnant women how their husbands felt when they have learnt about the index pregnancy. Paternal emotion during pregnancy and childbirth is imperative for better maternal and newborn health outcomes, though policy and strategic framework has been lacking in Ethiopia. Therefore, this study aimed to explore perceived paternal emotional fertility intentions of their husbands and/or their male partners and examine its correlates among a panel of pregnant women in Ethiopia. Methods Nationally representative data from cohort one baseline cross-sectional survey were used. A total of 2,115 pregnant women from a total of 217 enumeration areas were included in this further analysis. Frequencies were computed to describe pregnant women. Multinomial logistics regression statistical modeling was fitted to identify correlates of perceived paternal emotional fertility intentions. Results were presented in the form of percentages and odds ratio with 95% Confidence Intervals. Statistical significance was declared at a p-value of 0.05. Result The proportion of perceived paternal emotional fertility intentions of being a sort of happy and very happy were found to be (35.40%; 95%CI: 33.00%, 37.87%) and (49.03%; 95%CI: 46.48%, 51.6%) respectively. The likelihood of perceived paternal emotional fertility intentions of being very happy was (AOR: 95%CI: 5.06: (1.73, 14.85) and (AOR: 95%CI: 2.65: (1.67, 4.20) times higher among older pregnant women and those who intended having another child respectively. On the contrary, those with higher birth order, who wanted no more another child, those living as a partner and; those residing in Addis Ababa and SNNPR had (AOR: 95%CI: 0.25: (0.15, 0.40), AOR: 95%CI: 0.14: (0.07, 0.27); (AOR: 95%CI: 0.54: (0.33, 0.90), (AOR: 95%CI: 0.34: (0.17, 0.67), (AOR: 95%CI: 0.27: (0.14, 0.53) and AOR: 95%CI: 0.25: (0.15, 0.40) times lower likelihood of perceived paternal emotional fertility intention of being very happy about the index pregnancy respectively. The likelihood of perceived paternal emotional fertility intentions of being a sort of happy was found to be (AOR: 95%CI: 1.93 (1.21, 3.10) times higher among those wanting to have another child. This likelihood was found to be (AOR: 95%CI: 0.62 (0.43, 0.89), (AOR: 95%CI: 0.43 (0.22, 0.85) and (AOR: 96%CI: 0.45 (0.28, 0.74) times lower among those whose desired place of delivery was health facility, with higher birth order and residents of Oromiya region respectively. Conclusion Half of the pregnant women perceived that their husband felt very happy with calls up on a region specific age sensitive interventions in improving couples communication, and discussion on the spacing and timing of pregnancies as well as to work on improving childbirth preparedness and complication readiness. The ministry and relevant partners need to work strategically on male’s involvement in fertility desire along with emotional care and support. Women with future fertility intention, lower birth orders and those who have not legally married need to be targeted. Installing inter pregnancy preconception care package; improving counseling and provision of postpartum contraceptives; increasing men fertility knowledge and their emotional readiness; and lifestyle adjustment before pregnancy to improve psycho-social health during the perinatal period and paternal emotional fertility intentions are imperative.